Impacts of high-speed rail development on urban land expansion and utilization intensity in China - Xin Li; Xiaodong Ma (Journal of Transport and Land Use)
Urban land expansion (ULE) is a crucial factor for socioeconomic and environmentally sustainable development. However, nowadays, the unprecedented scale of high-speed railway (HSR) construction in China could exert an important influence on ULE. This manuscript first reveals the influence mechanism of HSR on ULE and then employs difference-in-difference (DID) models to investigate this effect based on the data of 280 prefectures and above level cities of 2001-2016. We analyze that HSR exerts a joint effect on ULE from the territorial and local levels and then affects urban land-use intensity (ULUI). HSR opening and HSR station distance both have notably positive effects on ULE, with elastic coefficients of 4.1% and 0.5%, respectively. HSR opening and HSR station distance also both exert positive effects on ULE of the central, eastern region cities and large cities of China, while for the western region and small to medium cities, they are not significant. The impact of HSR station distance on ULUI is negative with a significance level of 0.073, while the impact of HSR opening on ULUI is not significant. Lastly, relevant policy implications are proposed to alleviate urban land waste and spatial disequilibrium under the context of HSR building. This study can provide an important basis for sustainable urban land allocation.